Characteristics of HPV infection over time in European women who are HIV‐1 positive. Issue 1 (2nd November 2012) - Heard, I; Cubie, HA; Mesher, D; Sasieni, P; ,
<x xml:space="preserve">Abstract</x> Objective The objectives of the study were to investigate high‐risk human papillomavirus (HR‐HPV) infection and type distribution in women infected with HIV‐1, and to determine the relevance of HR‐HPV positivity and persistence/loss to the development of high‐grade cervical disease. Design A total of 518 European women infected with HIV attending for routine gynaecological care consented to 6‐monthly follow‐up visits over 3 years, with surveillance of cytology, colposcopy and histopathology, where relevant, and longer follow‐up, where possible. Setting European women infected with HIV attending for routine gynaecological care. Population or sample 518 European women infected with HIV attending for gynaecological care in 6 hospital‐based European centres ‐ Dublin, Edinburgh, London, Milan, Paris, and Warsaw. Methods Cervical screening was achieved by liquid‐based cytology (LBC) of brush samples in PreservCyt® medium. The HPV testing of residual samples was performed by Hybrid‐Capture II, with genotyping of positives using the HPV Line Blot Assay. Histology results were accessed where available. Main outcome measures Description of high risk human papillomavirus (HR‐HPV) infection and type distribution in HIV‐1 infected women. Results The estimated prevalence at baseline of any HR‐HPV type was 49.5% (46.3–52.8%): 10.2% for HPV 16 and 4.3% for HPV 18. The prevalence increased with increasing immunosuppression. Multiple infections were detected in 26.8%. HR‐HPV genotypes were detected in 34.9% of cases with normal cytology, in 77.2% of cases with atypical squamous cells of undetermined significance/low‐grade squamous intraepithelial lesion (ASCUS/LSIL) and in 90.8% of cases with high‐grade SIL (HSIL). The prevalence of HPV 16 in HSIL was 38.5%, with the three most common types thereafter having prevalence rates of 19.2% (HPV 58), 19.2% (HPV 53) and 16.6% (HPV 52). The overall persistence of any high‐risk type was 55.8%. We found that 6 months persistence of HPV 16 occurred in 24 women. Seven cases of high‐grade cervical disease developed, and all were associated with initial/persistent HR‐HPV positivity. Conclusions A wide diversity of HPV types was evident, and multiple infections were common. Detection or persistence of any HR‐HPV was associated with a very low incidence of subsequent high‐grade disease.